Implementation of CRM (Customer Relationship Management) at UPT Public Health Center Perbaungan Web-Based - Beni Frandian; Yudhanata, Ridho Dwi; Samsudin, Samsudin; Suendri, Suendri (Ali Institute or Research and Publication, 2022)
Public health center is a health service facility that organizes health efforts for the community. Currently, most public health center are still using the old system to record all transaction results, and the data processing is still in manual form so that this method can be time consuming and inefficient. Therefore, the researcher intends to find out and analyze the effect of service quality on patient satisfaction with the customer relationship management method. One of the things that health workers need to know and pay attention to is efforts to improve the quality of services that can have an impact on the good or bad of the patient's assessment of the public health center. The stages of data collection were carried out by conducting interviews, literature studies, and observations. and using the RAD method at the system development stage. The application of the Customer Relationship Management method at the UPT Public health center Perbaungan was built on a web-based basis, with the CRM application it is expected to help attract new patients and also maintain the quality of services provided to patients so that they can continue to assist the marketing process for service satisfaction at the Public health center.